EMPOWERING LOCAL COMMUNITIES THROUGH COMMUNICATIVE ENGLISH TRAINING IN TOURISM VILLAGE - Maknun, Lu'luil; Restu Arini; Valentina Dyah Arum Sari (JURNAL PENGABDIAN MANDIRI, 2025)
Tourism village development in Central Java continues to drive economic growth; however, limited English proficiency among rural tourism actors restricts their ability to fully engage in global tourism opportunities. This community service program aimed to empower residents of Makukuhan Kembang Madu Tourism Village, Temanggung, through communicative English training tailored to real tourism interactions. A total of 35 participants aged 16–45, representing various tourism-related occupations, joined an eight-week training built upon Communicative Language Teaching (CLT) principles. Contextual materials, including product storytelling, homestay communication, and mock tour-guiding, were integrated with local cultural content to foster identity expression and relevance to community livelihoods. Mixed evaluation methods, comprising pre- and post–assessments, classroom observations, and informal interviews, were employed to examine the outcomes. Results showed notable improvement in functional speaking skills, vocabulary recall, and participant confidence, confirmed by increased willingness to interact with simulated foreign tourists and use English to promote local products. Learners also reported increased cultural pride and a greater readiness to engage in tourism-related entrepreneurship. The findings highlight that community-based, context-driven English training can significantly enhance communication competence and socio-economic preparedness in rural tourism settings. Sustainability efforts include continued volunteer-led learning sessions and community learning resources. Future programs are recommended to extend their duration, apply differentiated instruction, and incorporate digital learning support to further strengthen long-term empowerment and tourism competitiveness in the region.